Hereditary Angioedema: The Economics of Treatment of an Orphan Disease - Lumry, William Raymond (Frontiers in Medicine, 2018)
This review will discuss the cost burden of HAE on patients, healthcare systems, and society. The impact of availability of and access to novel and specific therapies on morbidity, mortality and the overall burden of disease will be explored along with potential changes in treatment paradigms to improve effectiveness and reduce cost of treatment. The prevalence of orphan diseases, legislative incentives to encourage development of orphan disease therapies and the impact of orphan disease treatment on healthcare payment systems will be discussed.